2016
DOI: 10.1177/1524839916676073
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Preventive Measures in Public Nursery Schools: Lessons From the H1N1 Pandemic

Abstract: Nursery schools serve as reservoirs of transmission of infectious diseases, and teachers should be able to implement and monitor hygiene measures to prevent them. The aim of the present study was to assess the compliance of nursery school teachers on promoting preventive interventions and to identify associated factors, during the novel H1N1 influenza pandemic. A secondary objective was to evaluate their knowledge and vaccination status regarding the novel virus. A cross-sectional study was performed, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…This vaccination was characterized as an expression of social responsibility, albeit optional, as it was intended both for their personal protection and protection of the students. Worldwide few studies have aimed to explore attitudes, knowledge and vaccination coverage of school teachers and the majority of them have focused on measles and influenza vaccination [ 2 3 4 5 ]. The general conclusion is that teachers have a lower than expected vaccine acceptance rate which may be improved with targeted education [ 2 3 4 5 ].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…This vaccination was characterized as an expression of social responsibility, albeit optional, as it was intended both for their personal protection and protection of the students. Worldwide few studies have aimed to explore attitudes, knowledge and vaccination coverage of school teachers and the majority of them have focused on measles and influenza vaccination [ 2 3 4 5 ]. The general conclusion is that teachers have a lower than expected vaccine acceptance rate which may be improved with targeted education [ 2 3 4 5 ].…”
mentioning
confidence: 99%
“…Worldwide few studies have aimed to explore attitudes, knowledge and vaccination coverage of school teachers and the majority of them have focused on measles and influenza vaccination [ 2 3 4 5 ]. The general conclusion is that teachers have a lower than expected vaccine acceptance rate which may be improved with targeted education [ 2 3 4 5 ]. Studies have also shown that teachers may have an important role in addressing students' and parents' vaccine hesitancy and this role has been found to be associated with their own knowledge, attitudes and practices towards vaccines [ 5 6 7 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…También se han evaluado los conocimientos y actitudes en docentes en pandemias anteriores como la ocasionada por el H1N1, lo anterior para conocer si los profesores identifican factores de riesgo y medidas de intervención para promocionar la prevención en los lugares de trabajo, debido a que en estos se pueden transmitir las enfermedades debido a sus características, los investigadores reportaron bajo nivel de conocimientos y recomendaron mejorar la comunicación y sobre todo aclarar los miedos relacionados con la vacuna. En el primer párrafo de la discusión del artículo publicado por Michail y colaboradores, ellos mencionado que los profesores pueden influir en los hábitos de sus estudiantes, por consiguiente, es muy importante que ellos tengan conocimientos y actitudes convenientes para fomentar esto en la comunidad educativa y en general en la sociedad (Michail et al, 2017).…”
Section: Facceaunclassified